Sunflower Plants as Bioindicators of Environmental Pollution with Lead (II) Ions - Krystofova, Olga; Shestivska, Violetta; Galiova, Michaela; Novotny, Karel; Kaiser, Jozef; Zehnalek, Josef; Babula, Petr; Opatrilova, Radka; Adam, Vojtech; Kizek, Rene (Sensors (Basel, Switzerland), 2009)
In this study, the influence of lead (II) ions on sunflower growth and biochemistry was investigated from various points of view. Sunflower plants were treated with 0, 10, 50, 100 and/or 500 μM Pb-EDTA for eight days. We observed alterations in growth in all experimental groups compared with non-treated control plants. Further we determined total content of proteins by a Bradford protein assay. By the eighth day of the experiment, total protein contents in all treated plants were much lower compared to control. Particularly noticeable was the loss of approx. 8 μg/mL or 15 μg/mL in shoots or roots of plants treated with 100 mM Pb-EDTA. We also focused our attention on the activity of alanine transaminase (ALT), aspartate transaminase (AST) and urease. Activity of the enzymes increased with increasing length of the treatment and applied concentration of lead (II) ions. This increase corresponds well with a higher metabolic activity of treated plants. Contents of cysteine, reduced glutathione (GSH), oxidized glutathione (GSSG) and phytochelatin 2 (PC2) were determined by high performance liquid chromatography with electrochemical detection. Cysteine content declined in roots of plants with the increasing time of treatment of plants with Pb-EDTA and the concentration of toxic substance. Moreover, we observed ten times higher content of cysteine in roots in comparison with shoots. The observed reduction of cysteine content probably relates with its utilization for biosynthesis of GSH and phytochelatins, because the content of GSH and PC2 was similar in roots and shoots and increased with increased treatment time and concentration of Pb-EDTA. Moreover, we observed oxidative stress caused by Pb-EDTA in roots where the GSSG/GSH ratio was about 0.66. In shoots, the oxidative stress was less distinctive, with a GSSG/GSH ratio 0.14. We also estimated the rate of phytochelatin biosynthesis from the slope of linear equations plotted with data measured in the particular experimental group. The highest rate was detected in roots treated with 100 μM of Pb-EDTA. To determine heavy metal ions many analytical instruments can be used, however, most of them are only able to quantify total content of the metals. This problem can be overcome using laser induced breakdown spectroscopy, because it is able to provide a high spatial-distribution of metal ions in different types of materials, including plant tissues. Data obtained were used to assemble 3D maps of Pb and Mg distribution. Distribution of these elements is concentrated around main vascular bundle of leaf, which means around midrib.
Keywords: phytoremediation; heavy metals; spectrometry; laser induced breakdown spectroscopy; high performance liquid chromatography with electrochemical detection; sunflower; lead ions